Process Costing in Perspective: Forget Fifo. - Horngren, Charles T.; Churchill, Neil C. (The Accounting Review, 1967)
This article focuses on the product-costing aspects of process costing. First-in, first-out (Fifo) process costing has been overemphasized in cost accounting texts and in the Certified Public Accountants examination; it should be pruned from major consideration in courses and examinations. Fifo process costing is unnecessarily complex, is not used in practice, and is theoretically weak. Before examining the reasons for this position, it should be noted that this article concentrates on the product-costing aspects of process costing. It is concerned only incidentally with planning and control. By definition, process costing is a type of product costing that deals with the mass production of like units which usually move in continuous fashion through a series of manufacturing steps called operations or processes. The complexities and conflicts between weighted-average and Fifo costing methods are eliminated by using standard costs.